A hybrid metaheuristic method for optimization of active tuned mass dampers. (12th November 2021) - Kayabekir, Aylin Ece; Nigdeli, Sinan Melih; Bekdaş, Gebrail
Abstract: A metaheuristic‐based tuning methodology for the optimization of active tuned mass dampers (ATMDs) is presented. The methodology considers both physical parameters of ATMDs and controller parameters of the control algorithm. The employed control algorithm is a proportional–integral–derivative type controller. ATMDs are used in structures in the reduction of structural responses resulted from earthquakes. The proposed methodologies must be feasible for real practices in construction, so consider all physical factors such as stroke capacity, limitation of the active control force, the time delay of the generated control signal, and a time‐saving one. A novel hybrid metaheuristic algorithm that combines the specific advantages of four metaheuristics (harmony search, flower pollination algorithm, teaching‐learning‐based optimization and Jaya algorithm) is proposed for the optimization process. The results of the process showed that ATMDs are more effective for high values strike limitations, compared to TMDs. The feasibility and effectiveness of the optimum control method are also demonstrated on a full‐size 76‐story structure.